A Review on Halide Perovskites as Color Conversion Layers in White Light Emitting Diode Applications. Issue 13 (18th May 2018) - Guner, Tugrul; Demir, Mustafa M.
Abstract : In the last decade, halide perovskites have attracted great interest due to many reasons, including their low cost, solution‐processability, superior PL properties, broad range of color tunability, color purity, and defect tolerance, among others. They are in increasing demand for a wide range of applications, such as solar cells, light emitting diodes (LEDs), white LEDs (WLED), and lasers. Yellow phosphors have been heavily employed in solid‐state lighting, since its illumination by blue yields white light with various optical features, such as high/low CRI, CCT, and luminous efficiency. However, phosphors as pigments are seldom found and are costly material. In this sense, halide perovskites may offer a promising alternative to phosphors for future solid‐state lighting. In this study, the synthesis and optical properties of halide perovskites, as well as their application in WLED as a conversion layer are investigated. Abstract : Halide perovskites are promising materials that can be readily employed in color conversion layers as alternative to phosphors for white light generation. It is expected for these materials to surpass the phosphor‐related studies in a short time, and then lead to rapid growth for halide perovskites in fabrication of white LEDs.